Cumplimiento del principio de suficiencia recaudatoria en la provincia de El Oro en el periodo 2015-2016. - Heras Macas, Ligia Andrea (2017)
The following paper has as an objective to analyze the compliance with the principle of sufficiency of tax collection in the province of El Oro, taking into account that the information provided by the SRI (Internal Revenue Service) provided us the necessary guidelines to be based on the statistical information of the national tax collection and in El Oro province, it is possible to analyze if the principle which is the object of study is being fulfilled in its entirety, it is for this reason that the research is a descriptive due to the application of chapters and statistical tables with variations in the years 2015-2016, as well as the collection targets proposed for the province and the current levels of collection obtained. In 2015 in Ecuador, there was a significant variance in the Iva percentage (from June 2016 to May 31, 2017) the IVA rate from 12% to 14% and in June 2017 returned to 12%. The study found a significant difference level in collections in this specific tax. The Ecuadorian tax legislation foresees supposed numbers of elimination or reduction of the payment of tax obligation to promote objectives of the policy of control of the collected and what will be collected, which will be used for the benefit of the state. Incentives and benefits from various forms in a simplified scheme of tax calculation, in any case it will be done by exemptions of income, consumption and certain patrimonial elements; deductions to the tax base, tax rates, among others. In addition, it must be taken into account that in order to carry out the approximations of collection, it is necessary to analyze what has been collected in previous years and what is currently collected and to draw an acceptable variation of collection, which can be verified in chapter IV, where it will be able to display the goal of Collection of 215 and 2016, and the proceeds of those same years and thus specify whether the 100% target is met comparing previous years in terms of tax. Taxes contribute to tax expenditures with the purpose of making a better allocation for the general income of the state, privatizing the security of collected values, to promote the employment and investment, according to the Constitution of Ecuador Art. 300 of the Tax Regime which contemplates the Principles of Generality , Progressivity, Efficiency, Administrative Simplicity, Nonretroactivity, Equity, Transparency and Collective Sufficiency, through these principles the legislation establishes the direction of the national tax system, being the aim of study in this investigation the principle of sufficiency of collection. The methodology used is descriptive because through statistical data we will reveal changes in collections and the percentage that represents the same in order to determine if the principle established in the investigation is met; In addition to the study of norms, regulations, laws and referential documentation on the figures of the General Proforma of the Budget, they include the national and provincial account surrender rates for the period 2015-2016. Therefore, the information provided by the Internal Revenue Service in its WEB Portal, it allows at the same time to know tax and legal provisions related to the subject being evaluated, that is why according to what was analyzed, what or how much? Is a sufficient collection and how much would be the minimum percentage or minimum variant so that the principles established by law are fulfilled. As a result, to determine if the Principle of Sufficiency Collection is met or not, based on the analysis of compliance with the collection targets of the periods studied; After having collected the information and analyzed it, it was possible to appreciate that the collection goal is only fulfilled in 95% by 2015 and by 2016 only in 92% which results, in view of the premise raised regarding the Principle Of Recovering Sufficiency, that it is not fulfilled as it has not been able to reach the collection goal.